Advantages and disadvantages of hormone replacement therapy - Bebar, Sonja (Radiology and oncology (Ljubljana), 1996)
In the developed countries, more than 30% of female population is in the postmenopusal period of their life. Approximately one third of these present with severe clinical menopausal symptoms, such as hot flushes, sleeplessness, night sweats, and depression. Many women search medical help. By means of hormone replacement therapy (HRT), these problems can be either completely eliminated or alleviated in 90% of women. The suspected association between HRT and risk of carcinoma should be ignored, however. While estrogens in combination with progestogens exert a protective effec against ovarian and endometrial carcinomas, a possible correlation between HRT and breast cancer has not been fully explained yet. Nevertheless, some published reports have indicated a slightly increased risk of breast cancer after a prolonged use of HRT.
Keywords: Adverse effects; Breast neoplasms; Endometrial neoplasms; estrogen; Estrogen replacement therapy; Gastrointestinal neoplasms; ginekologija; hormoni; Neoplasms; Ovarian neoplasms; Risk factors; zdravljenje; ženske